A systematic review on recurrent respiratory papillomatosis: clinical effect and duration of benefit of different treatment modalities - Elina Kiverniti; Nick Sevdalis; Anastasia Rachmanidou-Doran (Frontiers Media S.A., 2011)
The aim of this study is to compare different modalities used for the treatment of recurrent respiratory papillomatosis (RRP) in adults and children in terms of their clinical effect and the duration of benefit. Systematic review of papers was written in the English language and published between 1977 and 2007. Outcomes are number of patients with a clinical response and length of time the response lasted for. We found 28 useful studies. There were 1,045 subjects, 416 children and 339 adults who underwent different treatments for RRP between 1976 and 2007. The methods used consisted of cidofovir, interferon, surgical excision, indole-3-carbinol, acyclovir, mumps vaccine, and photodynamic therapy. 62.5% of patients had a complete response on cidofovir (11 studies), 45.14% on interferon (8 studies), 33.33% on I3C (2 studies), 44.36% after surgery (5 studies), 77.55% after the mumps vaccine (1 study), 100% on acyclovir (1 study), and 9.09% after photodynamic therapy (1 study). The effect of different modalities lasted between 9 and 27 months. In conclusion, it is impossible to reach any reliable conclusions as to which method is the most durable and effective. There is a great need for randomised control multicentre trials on the treatment of RRP, so that reliable results can be produced.